2016
DOI: 10.18226/23190639.v3n3.05
|View full text |Cite
|
Sign up to set email alerts
|

A Colaboração Na Cadeia De Suprimentos, as Capabilidades E O Desempenho Operacional: Uma Análise No Setor De Bens De Capital

Abstract: Resumo O objetivo deste estudo foi verificar a importância das práticas da colaboração, caracterizadas como compartilhamento de recursos, informações, objetivos comuns, as capabilidades operacionais e o desempenho operacional nas empresas do setor de bens de capital, instaladas no Brasil. Para este estudo foi considerada a cadeia de suprimentos direta, no relacionamento de colaboração entre a empresa foco ou principal e os seus fornecedores de primeira camada. A pesquisa foi dividida em duas fases. Na primeira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Regarding quality, Domenek & Moori (2016) pointed out as the main performance factor acquired as a result of collaboration processes should be implemented.…”
Section: Operational Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Regarding quality, Domenek & Moori (2016) pointed out as the main performance factor acquired as a result of collaboration processes should be implemented.…”
Section: Operational Performancementioning
confidence: 99%
“…The results showed that the resolution and measurement of problems, besides joint planning between suppliers and customers, are fundamental for the development of a collaborative culture in the supply chain. Domenek & Moori (2016) aimed to analyze the importance of collaborative practices characterized as the sharing of resources and information, common objectives, operational capabilities, and operational performance in companies in the capital goods sector in Brazil. The research was divided into interviews with 10 managers of multinational companies and questionnaires applied to 40 companies in the sector.…”
Section: Operational Performancementioning
confidence: 99%